2020
DOI: 10.3389/fphar.2020.523962
|View full text |Cite|
|
Sign up to set email alerts
|

Moringa oleifera Alkaloids Inhibited PC3 Cells Growth and Migration Through the COX-2 Mediated Wnt/β-Catenin Signaling Pathway

Abstract: Moringa oleifera Lam. (M. oleifera) is valuable plant distributed in many tropical and subtropical countries. It has a number of medicinal uses and is highly nutritious. M. oleifera has been shown to inhibit tumor cell growth, but this effect has not been demonstrated on prostate cancer cells. In this study, we evaluated the inhibitory effect of M. oleifera alkaloids (MOA) on proliferation and migration of PC3 human prostate cancer cells in vitro and in vivo. Furthermore, we elucidated the mechanism of these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…Moringa oleifera ( M. oleifera ) is native to India, and it is widely planted and used in tropical and subtropical areas in recent decades, due to its high nutritive values in proteins, amino acids, fats, minerals, and vitamins ( 3 ). In contrast, the complex and diverse chemical components including flavonoids, phenolic acids, glucosinolates, and nitrile glycosides in M. oleifera lead to its numerous pharmacological activities, for example, antioxidant ( 4 ), anti-inflammatory ( 5 ), antibacterial ( 6 ), anticancer ( 7 ), hypoglycemic ( 8 ), and hypolipidemic ( 9 ) activities. Therefore, M. oleifera has received increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera ( M. oleifera ) is native to India, and it is widely planted and used in tropical and subtropical areas in recent decades, due to its high nutritive values in proteins, amino acids, fats, minerals, and vitamins ( 3 ). In contrast, the complex and diverse chemical components including flavonoids, phenolic acids, glucosinolates, and nitrile glycosides in M. oleifera lead to its numerous pharmacological activities, for example, antioxidant ( 4 ), anti-inflammatory ( 5 ), antibacterial ( 6 ), anticancer ( 7 ), hypoglycemic ( 8 ), and hypolipidemic ( 9 ) activities. Therefore, M. oleifera has received increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In the regulation of cell cycle phase, the nets work of cyclin-dependent kinases (CDKS) plays an important role. Cyclin E is a key regulator involved in the G1/S phase of the cell cycle ( Xie et al, 2020 ). P21 and P27 were cyclin-dependent kinases inhibitors (CDKIS) that inhibited the activity of CDKS ( Lee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, M. oleifera leaves can treat colitis; 21 M. oleifera alkaloids can be used to treat prostate cancer, and some ingredients in M. oleifera have been shown to exhibit DPP-IV inhibitory activity. 22,23 We have shown that M. oleifera seed ultrafiltration peptide components (<3 kDa) exhibit good hypoglycemic activity, but the specific peptide components and their physical and chemical properties have not yet been described.…”
Section: Introductionmentioning
confidence: 99%